2019
DOI: 10.1111/ipd.12590
|View full text |Cite
|
Sign up to set email alerts
|

The relative frequency of paediatric oral and maxillofacial pathology in New Zealand: A 10‐year review of a national specialist centre

Abstract: Background There has been no previous report of the prevalence of paediatric oral and maxillofacial pathology in a New Zealand oral pathology diagnostic service. Aim The aim of this study was to review cases of paediatric oral pathology to determine relative frequencies of oral lesions in this age group. Design Paediatric oral pathology cases (≤15 years of age) received between 2007 and 2016 were retrieved from the electronic database of the Oral Pathology Centre, University of Otago. Data collected included d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 17 publications
(140 reference statements)
2
3
0
2
Order By: Relevance
“…Regarding OPMD and ML, there was a greater preponderance at older ages, noting that in the young group only BL were seen as the most common, while in the elderly group ML are already part of the most frequent pathologies. These data are consistent with the literature, where advanced age is an important non-modifiable risk factor for oncological diseases ( 3 , 13 - 18 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Regarding OPMD and ML, there was a greater preponderance at older ages, noting that in the young group only BL were seen as the most common, while in the elderly group ML are already part of the most frequent pathologies. These data are consistent with the literature, where advanced age is an important non-modifiable risk factor for oncological diseases ( 3 , 13 - 18 ).…”
Section: Discussionsupporting
confidence: 93%
“…In the young group, from 0 to 17 years of age, the mucocele stood out, being more common in males, with preferential location in the lower lip, which is consistent with other data ( 18 , 22 ). This frequency may it will be explained by the fact that earlier ages are more associated with possible trauma that could be the origin of this entity.…”
Section: Discussionsupporting
confidence: 91%
“…The prevalence of paediatric oral and maxillofacial lesions and their corresponding studies varies globally, demonstrated by the variation of children's ages included in the studies, lengths of study, and various classifications of oral and maxillofacial lesions in the respective studies 1‐15 . Through this study it can be surmised that globally, the prevalence of paediatric oral and maxillofacial lesions ranges between 2.6% and 19.3% in patients between 0 and 19 years old.…”
Section: Introductionmentioning
confidence: 77%
“…소아 청소년의 구 강 병소에 관한 기존의 연구들은 대부분 종양을 비롯한 특정 질 환에만 초점을 두고 있으며 [2][3][4], 전반적인 구강 병소의 생검 결 과를 보고한 연구는 많지 않다. 북미 [5][6][7][8], 남미 [9][10][11][12][13][14][15], 유럽 [16][17][18], 아프리카 [19,20], 호주와 뉴질랜드 등 전 세계 각 지역에서 소아 청소년 환자의 구강 병소 생검 결과를 후향적으로 분석하 였으며 [21][22][23], 아시아에서는 태국 [24][25][26], 인도 [27], 사우디아라 비아 [28], 이란 [29], 대만에서 주로 연구되었다 [30][31][32]. 국내에서 는 치성 종양에 한정하여 전 연령대에서 시행된 생검 결과에 관 한 연구는 보고된 바 있으나 [33] 계를 고려하고 선행 연구의 연구 설계를 참고하여 세 집단으로 나누었다: 1) 0 -5세(유치열기); 2) 6 -11세(혼합치열기); 3) 12 -16세(영구치열기) [6,8,14,18,19,24,26].…”
Section: ⅰ 서 론unclassified